The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.5194/cpd-4-897-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Western Europe is warming much faster than expected

Abstract: Abstract. The warming trend of the last decades is now so strong that it is discernible in local temperature observations. This opens the possibility to compare the trend to the warming predicted by comprehensive climate models (GCMs), which up to now could not be verified directly to observations on a local scale, because the signal-to-noise ratio was too low. The observed temperature trend in western Europe over the last decades appears much stronger than simulated by state-of-the-art GCMs. The difference is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
124
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(139 citation statements)
references
References 22 publications
13
124
0
2
Order By: Relevance
“…1a). The change in SAT during the recent 16 years (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) relative to the early period 1964-1993 ranges from 0.93 to 1.10 °C from four data sets, consistent with previous studies (Ruckstuhl et al 2008;Philipona et al 2009;van Oldenborgh et al 2009). The rapid summer mean warming over Western Europe was also accompanied by changes in temperature extremes.…”
Section: Observed Changes In Summer Mean Temperature and Temperature supporting
confidence: 78%
See 1 more Smart Citation
“…1a). The change in SAT during the recent 16 years (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) relative to the early period 1964-1993 ranges from 0.93 to 1.10 °C from four data sets, consistent with previous studies (Ruckstuhl et al 2008;Philipona et al 2009;van Oldenborgh et al 2009). The rapid summer mean warming over Western Europe was also accompanied by changes in temperature extremes.…”
Section: Observed Changes In Summer Mean Temperature and Temperature supporting
confidence: 78%
“…Understanding the nature and drivers of this variability is an essential step in developing robust climate predictions and risk assessments. In the last few decades, Europe has warmed not only faster than the global average, but also faster than expected from anthropogenic greenhouse gas increases (Ruckstuhl et al 2008;Philipona et al 2009;van Oldenborgh et al 2009). With the warming, Europe experienced record-breaking heat waves and extreme temperatures that imposed disastrous impacts on individuals, and society (Stott et al 2004;Fischer and Schär 2010;Barriopedro et al 2011;Christidis et al 2011Christidis et al , 2012Hegerl et al 2011;Rahmstorf and Coumou 2011;Hoerling et al 2012;Schubert et al Abstract Analysis of observations indicates that there was a rapid increase in summer (June-August) mean surface air temperature (SAT) since the mid-1990s over Western Europe.…”
Section: Introductionmentioning
confidence: 99%
“…The median is always in between these tendencies. These seasonal warming patterns agree well with results from other studies, which attribute them to snow and soil moisture effects (Seneviratne et al 2006;Diffenbaugh et al 2007;van Oldenborgh et al 2009). A stronger warming of the hot tails of temperature distributions with decreasing soil moisture content is also a feature found in observations from Southeastern Europe .…”
Section: Temperaturesupporting
confidence: 81%
“…The additional possibility of biases and changes in LSMPs affecting extreme temperatures must be considered in light of these and other mechanisms. For example, van Oldenborgh et al (2009) found that changes in the large-scale circulation, including a shift towards a more westerly circulation and the North Atlantic current need to be better simulated especially in winter and spring for more realistic simulations of warming over Western Europe in recent decades. Gershunov and Guirguis (2012) noted that three out of four GCMs analyzed did not adequately capture the synoptic causes of California heat waves.…”
Section: Projected Trendsmentioning
confidence: 99%